2017
DOI: 10.5539/jel.v6n3p299
|View full text |Cite
|
Sign up to set email alerts
|

Middle Grade Students’ Concept Images of Algebraic Concepts

Abstract: This study investigates middle school students' concept images of algebraic concepts which are term, constant term, variable, and coefficient. Also, the study aimed to explore their performances in defining these concepts correctly. A phenomenological method was used to support methodological perspective and to reveal the findings of the study. Twenty seven 7th grade students completed a questionnaire, which aims to assess students' concept images of the algebraic concepts. Twelve of them were selected for sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
0
1
0
3
Order By: Relevance
“…Accordingly, there is a positive association between conceptual knowledge and academic achievement in mathematics (Zakaria et al, 2010). • The lack of conceptual knowledge leads to a variety of challenges for students (Tekin-Sitrava, 2017). Hussein and Csíkos (2021) revealed that secondary school students in Erbil city had many problems with the concept of function.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Accordingly, there is a positive association between conceptual knowledge and academic achievement in mathematics (Zakaria et al, 2010). • The lack of conceptual knowledge leads to a variety of challenges for students (Tekin-Sitrava, 2017). Hussein and Csíkos (2021) revealed that secondary school students in Erbil city had many problems with the concept of function.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Veri toplama araçları olarak öğrencilerin kavram imajlarını belirleyebilmek için 4 açık uçlu sorudan oluşan Kavram Bilgi Formu (KBF) ve bu kavramlara yönelik 2 örnek sorudan oluşan Uygulama Formu (UF) kullanılmıştır. Formlar oluşturulurken literatürde kavram imajları belirlemede kullanılan veri toplama araçları (Attorps, 2003;Tekin Sitrava, 2017b) incelenerek bu kapsamda sorular oluşturulmuş ve eğitim alanında uzman iki akademisyenin görüşüne sunulmuştur. Uzman görüşü doğrultusunda formlara son hali verilip uygulamaya hazır hale getirilmiştir.…”
Section: Veri Toplama Araçlarıunclassified
“…Çalışmada elde edilen diğer bir sonuca göre öğrencilerin denklem ve özdeşlik ilişkisini belirlemede zorlandıkları, soruyu çoğunlukla boş bıraktıkları, hatırlayamayıp açıklayamadıkları veya bu kavramlar arasında ilişkinin olduğunu yazıp bunu belirtemedikleri görülmüştür. Bu kapsamda ulaşılan bu sonuç literatürde yer alan bazı çalışmalardaki farklı örneklem gruplarının cebir kavramları arası ilişkileri anlamada yeterli olmadıkları bulgusunu (Dane ve Başkurt, 2012;Dede, Bayazit ve Soybaş, 2010;Tekin Sitrava, 2017b) destekler niteliktedir. Mevcut çalışmada öğrencilerin denklem ve özdeşlik kavramları arasında benzer gördükleri ifadelerinin "bilinmeyenin olması, eşitlik ve değişkenin olması" temalarında yer aldığı belirlenmiştir.…”
Section: Sonuç Ve Tartışmaunclassified
See 1 more Smart Citation
“…Therefore, teaching mathematics conceptually is necessary for students to absorb mathematical subjects successfully (Andamon & Tan, 2018). While the lack of conceptual knowledge leads to a variety of challenges for students (Tekin-Sitrava, 2017).…”
Section: 4importance Of Conceptual Knowledge In Teaching Mathematicsmentioning
confidence: 99%